The impact of diet, physical activity, and sleep habits on obesity risk among female teachers in Lhokseumawe City - Cut Nurasiah; Etti Sudaryati; Zulhaida Lubis (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Unhealthy living behaviors and the double workload of female teachers have led to lifestyle changes that have an impact on the risk of obesity. This study aimed to determine the influence of diet, physical activity, and sleep habits on obesity risk among female teachers in Lhokseumawe. This cross-sectional study was conducted in Lhokseumawe City from November 2023 to April 2024 with 289 female teachers, using multistage random sampling. Eating patterns were measured using the semi-FFQ, physical activity using the International Physical Activity Questionnaire (IPAQ), sleeping patterns using the Pittsburgh Sleep Quality Index (PSQI), and body mass index (BMI) using anthropometric measurements. Bivariate analysis was performed using the chi-square test and multivariate analysis with multiple logistic regression. The results showed that Physical activity (p=0,023, RP=2,295) and fat intake (p=0,007, RP=0,484) influenced the incidence of obesity, whereas carbohydrate intake (p=0,622), energy (p=0,524), protein (p=0,225), food type (p=0,066), and sleep patterns (p=0,138) did not affect the incidence of obesity among female teachers in Lhokseumawe City. In conclusion, physical activity is the dominant risk factor for obesity. The risk of obesity was 2,295 times higher among female teachers who were not physically active.